- - Lolas Stepke, Fernando (Acta Bioethica, 2000)
This paper presents an approach to the process of valoric construction based on natural language, as characteristic of the world of life. It si suggested that this language reflects explicit and implicit anthropological conceptions within a given community. Drawing a parallel between attribution of meaning to words in the technosciences, the establishment of emotional lexica and valoric language, deliberation and dialogue -bioethical tools- are charged with the task of increasing moral constructivism in pluralistic societies and widening their creative options. This does not imply moral relativism but it points out the need to contextualize precepts and principles and to empirically study the forms in which dilemmas are articulated and solutions proposed. Some lines of development for a language-based empirical axiography are proposed as a legitimate component of social studies in bioethics.